2019
DOI: 10.12681/mms.19187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean acidification and warming on the feeding behaviour of two gastropod species

Abstract: Increased atmospheric CO2 produced by anthropogenic activities will be absorbed by the oceans over the next century causing ocean acidification and changes in the seawater carbonate chemistry. Elevated CO2 causes sublethal physiological and behavioural responses on the locomotion and foraging behaviour of marine organisms. This study aims to investigate the independent and synergistic effects of long term exposure to low pH and increased temperature on the feeding behaviour of two gastropod species, Hexaplex t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Nevertheless, previous studies, although based on different prey species, reported that the attacks by H. trunculus on small specimens of the mussel Brachidontes pharaonic (Fischer, 1870) (5–10 mm shell length) were completed in <4 h (Rilov et al, 2004). Also, Chatzinikolaou et al (2019) proved that ca. 45% of 10 days‐fasted H. trunculus successfully reached the offered food items in <1 h. Considering that the prey individuals used in our experiment had a length <15 mm and the shell of A. senhousia is more fragile than that of other mussels, we contend here that the duration of our experiment (24 h) could have not been an interfering factor.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous studies, although based on different prey species, reported that the attacks by H. trunculus on small specimens of the mussel Brachidontes pharaonic (Fischer, 1870) (5–10 mm shell length) were completed in <4 h (Rilov et al, 2004). Also, Chatzinikolaou et al (2019) proved that ca. 45% of 10 days‐fasted H. trunculus successfully reached the offered food items in <1 h. Considering that the prey individuals used in our experiment had a length <15 mm and the shell of A. senhousia is more fragile than that of other mussels, we contend here that the duration of our experiment (24 h) could have not been an interfering factor.…”
Section: Discussionmentioning
confidence: 99%
“…Ocean warming and acidification have been proven to affect physiological responses in marine molluscs (e.g., depression of metabolic rate, Bibby et al, 2007; alterations of immune responses and enzyme production, Matozzo et al, 2013), as well as behavioral responses related to predator avoidance (Bibby et al, 2007), reduction of feeding efficiency (Vargas et al, 2013) and movement restriction (Ellis et al, 2009). Hexaplex trunculus was less successful in reaching their food source under low pH (Chatzinikolaou et al, 2019). If such physiological and behavioral restrictions already deteriorate the ability of organisms to successfully cope with predation pressure, a thinner shell will certainly make the situation less favorable.…”
Section: Discussionmentioning
confidence: 99%
“…In marine gastropods, few works have assessed the long-term effects of acidi cation and warming. Research has focused on impacts on shell bio-mineralization and morphology (Rühl et al, 2017), feeding physiology and behaviour (Chatzinikolaou et al, 2019;Zhang et al, 2015); however, no study has assessed the combined effects of short-and long-term exposure to climate change in the physiology of marine gastropods.…”
Section: Introductionmentioning
confidence: 99%